Development of E-LKPD Science Materials on Physical Properties, Chemistry, and Changes Based on Ethnoscience in Red Brick Making - Zahra, Dhea Amalia; Desstya, Anatri (Universitas Muhammadiyah Surakarta, 2024)
Purpose: 1) Describe the process of developing E-LKPD science material on physical properties, chemistry, and its changes based on ethnoscience in red brick making and 2) Describe the level of validity of E-LKPD science material on physical properties, chemistry, and changes based on ethnoscience in making red bricks. Methodology: This type of research is Research and Development with the ADDIE model (analysis, design, development, implementation, evaluation) which is only limited to the development stage. The subjects of this research are one teacher at SDN Krikilan 2 Masaran, media expert validators and material expert validators. The data used in this study are two, namely qualitative data and quantitative data. Data collection techniques were carried out with questionnaires, interviews, validation sheets, and documentation. The data analysis technique used qualitative and quantitative data analysis techniques. Results: 1) The process of developing science E-LKPD products applies the ADDIE model by going through three stages, namely: analysis, which means analyzing the understanding of ethnoscience, the use of LKPD in elementary schools, print-based LKPD in the form of a needs analysis questionnaire. Design, namely making E-LKPD designs based on the constituent indicators. Development, is the step of making E-LKPD through canva which is then uploaded to the liveworksheets website to be used as an interactive LKPD. Furthermore, E-LKPD is validated by two validators, namely material expert validators and media experts to determine the validity level of the product. 2) The development of liveworksheets-based E-LKPD is feasible for educators to use in the learning process. The level of validity can be obtained through product validation test results. The results of validation on material experts obtained a percentage of 90% with very valid qualifications, media experts obtained a percentage of 87.5% with very valid qualifications. From this explanation, it can be concluded that the E-LKPD product is suitable for use in elementary school student learning activities. Applications/Originality/Value: In using this E-LKPD, it is necessary to prepare tools and materials that must be used by teachers and students.